2017
DOI: 10.1002/path.4923
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐migratory and TGF‐β‐activating functions of αvβ6 integrin in pancreatic cancer are differentially regulated via an Eps8‐dependent GTPase switch

Abstract: The integrin αvβ6 is up‐regulated in numerous carcinomas, where expression commonly correlates with poor prognosis. αvβ6 promotes tumour invasion, partly through regulation of proteases and cell migration, and is also the principal mechanism by which epithelial cells activate TGF‐β1; this latter function complicates therapeutic targeting of αvβ6, since TGF‐β1 has both tumour‐promoting and ‐suppressive effects. It is unclear how these different αvβ6 functions are linked; both require actin cytoskeletal reorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 51 publications
(85 reference statements)
0
32
0
Order By: Relevance
“…Furthermore, integrins also play a role in angiogenesis, by providing a docking site for several cell types, including endothelial cells, endothelial stem cells and inflammatory cells, at the site of angiogenesis [65]. Upregulation of amb6-integrins occurs in a variety of tumours, including PDAC, where it has been shown to activate TGF-b, stimulating tumour cell epithelial-to-mesenchymal transition (EMT) and stromal myofibroblast differentiation [66], which has in turn been shown to either promote [67] or restrict tumour growth and progression [68]. The association between amb6-integrins and increased migration, invasion and cell survival is partly due to the regulation of proteases (MMPs), and urokinasetype plasminogen activator (uPA) [63, 66,[69][70][71].…”
Section: The Src Signalling Axis Promotes Pancreatic Cancer Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, integrins also play a role in angiogenesis, by providing a docking site for several cell types, including endothelial cells, endothelial stem cells and inflammatory cells, at the site of angiogenesis [65]. Upregulation of amb6-integrins occurs in a variety of tumours, including PDAC, where it has been shown to activate TGF-b, stimulating tumour cell epithelial-to-mesenchymal transition (EMT) and stromal myofibroblast differentiation [66], which has in turn been shown to either promote [67] or restrict tumour growth and progression [68]. The association between amb6-integrins and increased migration, invasion and cell survival is partly due to the regulation of proteases (MMPs), and urokinasetype plasminogen activator (uPA) [63, 66,[69][70][71].…”
Section: The Src Signalling Axis Promotes Pancreatic Cancer Progressionmentioning
confidence: 99%
“…Upregulation of amb6-integrins occurs in a variety of tumours, including PDAC, where it has been shown to activate TGF-b, stimulating tumour cell epithelial-to-mesenchymal transition (EMT) and stromal myofibroblast differentiation [66], which has in turn been shown to either promote [67] or restrict tumour growth and progression [68]. The association between amb6-integrins and increased migration, invasion and cell survival is partly due to the regulation of proteases (MMPs), and urokinasetype plasminogen activator (uPA) [63, 66,[69][70][71]. In PDAC specifically, overexpression of integrin amb3/ amb6 has been previously shown to associate with poor survival of patients as well as lymph node metastasis [59,72], and recent findings indicate that the stromal localisation and levels of active a5b1-integrin and FAK can identify two readily distinguishable desmoplastic phenotypes in pancreatic cancer.…”
Section: The Src Signalling Axis Promotes Pancreatic Cancer Progressionmentioning
confidence: 99%
“…Relative to other fibronectin-binding integrins, αVβ6 exhibits distinct biophysical properties that promote force-generation, rigidity sensing and increase matrix stiffening 15 . Moreover, TGFβ is mechanically activated by αVβ6; requiring transmission of intracellular actomyosin-dependent forces to be applied on latent TGFβ via αVβ6 [32][33][34] .Biochemical integrin internalisation assays confirmed that EGF stimulation triggered endocytosis of αVβ6 ( Figure 6A). Therefore, we investigated whether αVβ6-EGFR crosstalk could regulate the ability of αVβ6 to transmit cytoskeletal mechanical forces to the extracellular environment.…”
Section: Egf Stimulation Suppresses αVβ6-mediated Force-application Omentioning
confidence: 92%
“…Therefore, we investigated whether αVβ6-EGFR crosstalk could regulate the ability of αVβ6 to transmit cytoskeletal mechanical forces to the extracellular environment. We performed traction force microscopy, using polyacrylamide hydrogels coated with the αVβ6-selective ligand LAP, to measure αVβ6-dependent mechanical force application 32 . These assays revealed that stimulation with EGF induced a marked suppression in the ability of MDA-MB-468 cells to apply αVβ6-dependent mechanical force on LAP ( Figure 6B).…”
Section: Egf Stimulation Suppresses αVβ6-mediated Force-application Omentioning
confidence: 99%
See 1 more Smart Citation